Organization and Methodological Support of Financial Monitoring in an Auditing Firm: New Requirements - Lubenchenko, О. Е. (Statistics of Ukraine, 2020)
The requirements to financial monitoring to be implemented by auditing entities, as defined by the Law of Ukraine “Preventing and Combating Legalization (Laundering) of Incomes Received by Criminal Ways, or Financing of Terrorism or Financing of Proliferation of Arms of Mass Destruction” from 06.12.2019 р. No 361-ІХ, enforced on 28.04.2020, are studied. The occurrence of ambiguous interpretations of some notions in the abovementioned Law or heavy financial sanctions that may be imposed on auditing entities entail the need in elaborated and implemented intra-firm documents on financial monitoring. While the previous revision of the Law contained the clearly defined peculiarities of organization of financial monitoring by auditing entities when providing certain services to clients (real estate transactions; asset management; raising of funds for establishing, operating and managing legal entities; sales and purchases of corporate assets), such peculiarities cannot be found in the new revision of the Law. It follows that now the auditing entities need to be guided by general norms of the Law in organizing financial monitoring. A series of administrative documents has been elaborated for this purpose: the order on appointment of a person responsible for financial monitoring; the conclusion of business reputation review for a candidate for the position of responsible person; the rules for financial monitoring of auditing entity; the monthly reference of the responsible person on the results of implemented actions on financial monitoring. The elaborated rules for financial monitoring cover all the legal requirements on implementation of financial monitoring, with the possibility of making amendments in them as appropriate. The rules must be informed to all the staff of an auditing entity, engaged in the provision of auditing and non-auditing services, through participation in internal training on financial monitoring issues. Apart from the rules, it is proposed that the working documentation supporting the procedures of financial monitoring should be supplemented by the following sections: 1. Documentary support for financial monitoring of auditing entities. 2. Staff and training of staff on financial monitoring issues. 3. Documentary support for interactions with the State Service of Financial Monitoring of Ukraine, ministries and administrative department, which allow auditing entities to meet fully the legal requirements and avoid heavy financial sanctions on the side of controlling and regulatory bodies.